The versatility of the pedicled medial sural artery perforator flap: from simple to its chimeric pattern and clinical experience with 37 cases - Scaglioni, Mario; Rodi, Timo; Fritsche, Elmar (Plastic and reconstructive surgery, 2021)
Background: - Defects in the knee area, popliteal fossa region, and upper third of the lower extremity can pose a challenge for reconstructive plastic surgeons. The purpose of this article is to report the authors’ experience with the use of the pedicled medial sural artery perforator flap in its simple and chimeric form for reconstruction of defects in three different regions: knee, popliteal fossa, and proximal lower leg. - Methods: From April of 2018 to April of 2019, 37 patients (29 men and eight women) with a mean age of 51 years (range, 18 to 78 years) underwent reconstruction with 37 pedicled medial sural artery perforator flaps. All flaps were harvested as pedicled perforator flaps in conventional or chimeric fashion and were based on one or two perforators. The defect locations included the knee (18 cases), popliteal fossa (seven cases), and proximal lower leg (12 cases). The cause of reconstruction was trauma in 22 patients (59 percent), tumor in 10 patients (27 percent), and donor-site closure of free medial sural artery perforator in five patients (14 percent). - Results: The flap sizes varied from 3.5 × 5 cm to 5 × 10 cm. All but one flap, which showed distal tip necrosis, survived completely after surgery. The donor sites were all closed primarily. Minor complications included flap dehiscence (two cases) and minor wound infection delaying the healing process (four cases). All complications were treated conservatively. Follow-up observations were conducted for 3 to 12 months, and all patients had good functional recovery with satisfactory cosmetic results. - Conclusion: - The pedicled medial sural artery perforator flap can be considered an optimal method of reconstruction for covering defects not only in the knee area but also in the popliteal fossa and upper lower leg. - CLINICAL QUESTION/LEVEL OF EVIDENCE: - Therapeutic, IV.
Gesehen am 07.06.2021